Arthroscopic Suture-Button Versus Hook-Plate Fixation for Acromioclavicular Joint Injuries-A Systematic Review of Comparative Studies - Angus J. Lloyd, M.B., B.Ch; Eoghan T. Hurley, M.B., B.Ch., M.Ch; Martin S. Davey, M.B., B.Ch., M.Ch; Leo Pauzenberger, M.D; Hannan Mullet, M.Ch., F.R.C.S.I. (Tr & Orth) (Elsevier, 2020)
Purpose: To systematically review the comparative studies in the literature to compare joint stability, clinical outcomes, and complications of acromioclavicular joint fixation using a hook plate versus arthroscopic suture-button (SB) fixation. Methods: A literature search was performed in accordance with the PRISMA guidelines to identify clinical studies comparing the hook plate and arthroscopic SB techniques for acromioclavicular joint injuries. Qualitative statistical analysis was performed using SPSS, and a P value of ≤.05 was considered to be statistically significant. Results: Six clinical studies including 285 patients were included in the systematic review. In 3 of the studies, there was a significant difference in favor of SB for Constant score. Patients treated with the SB technique had a lower visual analog scale score at final follow-up in 2 of the 4 studies that measured this outcome. In addition, there were no significant difference in the rate of complications, revisions, or joint malreduction in any of the included studies. Conclusions: The arthroscopic SB procedure resulted in lower postoperative pain scores, and improved postoperative functional outcomes, although this was not a clinically significant difference. In addition, there were no significant differences in the rate of complications, revisions, or joint malreduction. Level of Evidence: Level III, systematic review of Level I, II, and III studies.